Cerebellar Transcranial Direct Current Stimulation in People with Parkinson’s Disease: A Pilot Study - Craig D. Workman; Alexandra C. Fietsam; Ergun Y. Uc; Thorsten Rudroff (Brain Sciences, 2020)
People with Parkinson’s disease (PwPD) often experience gait and balance problems that substantially impact their quality of life. Pharmacological, surgical, and rehabilitative treatments have limited effectiveness and many PwPD continue to experience gait and balance impairment. Transcranial direct current stimulation (tDCS) may represent a viable therapeutic adjunct. The effects of lower intensity tDCS (2 mA) over frontal brain areas, in unilateral and bilateral montages, has previously been explored; however, the effects of lower and higher intensity cerebellar tDCS (2 mA and 4 mA, respectively) on gait and balance has not been investigated. Seven PwPD underwent five cerebellar tDCS conditions (sham, unilateral 2 mA, bilateral 2 mA, unilateral 4 mA, and bilateral 4 mA) for 20 min. After a 10 min rest, gait and balance were tested. The results indicated that the bilateral 4 mA cerebellar tDCS condition had a significantly higher Berg Balance Scale score compared to sham. This study provides preliminary evidence that a single session of tDCS over the cerebellum, using a bilateral configuration at a higher intensity (4 mA), significantly improved balance performance. This intensity and cerebellar configuration warrants future investigation in larger samples and over repeated sessions.